2022
DOI: 10.3390/ma15062031
|View full text |Cite
|
Sign up to set email alerts
|

Tool Wear Effect on Surface Integrity in AISI 1045 Steel Dry Turning

Abstract: In the present work, the surface integrity and flank wear of uncoated cermet inserts in dry turning of AISI 1045 steel were evaluated. Three-dimensional techniques were used to assess the surface roughness. Previously, finite element analysis was carried out to predict the cutting forces and heat distribution in the chip formation region. Cutting speed and feed were the parameters varied in the experiments. Feed is decisive in the final quality of the turned surface and cutting speed had little influence on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Excessive wear of cutting tool and hence short life of cutter are created due to generated heat in the cutting zone and dispersion of material expansion which can decrease the surface quality of machined components (Uzun et al 2022;Shalaby and Veldhuis 2019). Tool wear has an impact on not only tool life, but also the quality of the finished product in terms of dimensional accuracy as well as surface integrity of machined components (Magalhães et al 2022). Moreover, the ultimate surface roughness of machined components is one of the most essential factor in machining operations which should be investigated in terms of quality enhancement of machined parts (Hatefi and Abou-El-Hossein 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive wear of cutting tool and hence short life of cutter are created due to generated heat in the cutting zone and dispersion of material expansion which can decrease the surface quality of machined components (Uzun et al 2022;Shalaby and Veldhuis 2019). Tool wear has an impact on not only tool life, but also the quality of the finished product in terms of dimensional accuracy as well as surface integrity of machined components (Magalhães et al 2022). Moreover, the ultimate surface roughness of machined components is one of the most essential factor in machining operations which should be investigated in terms of quality enhancement of machined parts (Hatefi and Abou-El-Hossein 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Upadhyay et al [1] and González-Laguna, A. et al [24] extended the conclusion by analyzing the measured vibration signals. Based on the measured results it is concluded that the vibration properties, but also the roughness of the surface and the wear in turning [25], depend on the cutting tool parameters [26] and also on cutting parameters [27] e.g., speed, depth of cut, lubrication conditions and feed rate [12]. In addition, it is seen that based on the measured vibration properties of the system the prediction of the surface roughness is possible.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, experiments are done for workpieces made of various materials such as Ti-6Al-4V [1,2], dry grey cast iron [3], Inconel 718 alloy [4], stainless steel [5][6][7], for AISI 5140 [8], and AISI 316L steel for biomedical purposes [9]. The roughness properties of the turning EN19 steel, cut with the coated carbide tool [10], AISID2 turning with minimal quantity of lubrication (MQL) [11], dry turning [12] and hard turning of AISI 52100 steel [13], and Haynes 263 and Inconel 718 superalloys turning with cryogenic cooling [14] have also been considered. The obtained results show that the roughness level differs for various workpieces and turning properties and parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of operational parameters with rightly configured combination is an important criterion especially for dry finishing machining operations [25][26][27]. According to previous research work, for dry finishing turning operations depth of cut (DOC), feed rate (FR) and cutting speed (CS) are critical operational parameters [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%